EDUCATIONAL QUALITY ISSUES IN THE PROCESS OF DESIGNING LESSONS AIMING AT DEVELOPING CREATIVE THINKING BASED ON DIGITAL TECHNOLOGIES (Universal International Scientific Journal, 2026)
This article discusses the methodological foundations of designing lessons aimed at developing creative thinking in the modern educational process. This article analyzes pedagogical approaches that serve to form students' skills in independent thinking, finding unusual solutions, analyzing problem situations, and creating innovative ideas. It also substantiates the effectiveness of using interactive methods, a competency-based approach, and digital tools in lesson design. The results of the study show that lessons aimed at developing creative thinking significantly increase students' motivation, activity, and critical analysis skills. This article is of practical importance for educators, methodologists, and specialists seeking to apply innovative approaches in the educational process.
Keywords: Creative thinking, lesson planning, interactive methods in education, innovative pedagogy, effectiveness of the educational process, creative approach in education, pedagogical technologies.